An Abstraction Theory: A Bravery Perspective on Examining Effectiveness of Arts and Heritage Marketing Dimensions and Customer Value in Art Museums, Exhibits and Galleries in Egypt - Essam, Reem; Kortam, Wael; Tarek, Alaa (Journal of Marketing Development and Competitiveness, 2018)
The purpose of this research is to gain insight into the abstract marketing themes to make use of the best possible practices of the marketing departments at museums, illuminating the way for other researchers to establish additional studies that look deeply into the relationships among abstraction theory, art & heritage dimensions and customer value. The results of this research may start a debate on how and why the art and heritage field might move towards a stronger focus on abstract marketing throughout measurable results.